2016
DOI: 10.1007/s12034-016-1237-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mechanical and three-body abrasive wear peculiarity of TiO2- and ZnO-filled bi-directional E-glass fibre-based polyester composites

Abstract: This paper is about the development of bi-directional E-glass fibre-based polyester composites filled with zinc oxide (ZnO) and titanium dioxide (TiO 2) fillers, respectively. The mechanical characterization of these composites is performed. The three-body abrasive wear characteristic of fabricated composites has been assessed under different operating conditions. For this, the three-body abrasion test is done on dry abrasion test rig (TR-50) and analysed using Taguchi's experimental design scheme and analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Deneysel sonuçlarda; dolgu malzemelerinin ilavesi ile çekme mukavemetinin azaldığı fakat sertlik, eğilme mukavemeti, tabakalar arası kesme mukavemeti ve darbe mukavemeti gibi diğer mekanik özelliklerin arttığı görülmüştür. Diğer yandan TiO 2 dolgulu kompozitlerin ZnO dolgulu kompozitlere kıyasla daha iyi aşınma özellikleri sergilediği gözlemlenmiştir [56].…”
Section: C) çInko Oksitunclassified
“…Deneysel sonuçlarda; dolgu malzemelerinin ilavesi ile çekme mukavemetinin azaldığı fakat sertlik, eğilme mukavemeti, tabakalar arası kesme mukavemeti ve darbe mukavemeti gibi diğer mekanik özelliklerin arttığı görülmüştür. Diğer yandan TiO 2 dolgulu kompozitlerin ZnO dolgulu kompozitlere kıyasla daha iyi aşınma özellikleri sergilediği gözlemlenmiştir [56].…”
Section: C) çInko Oksitunclassified
“…It was seen that tensile strength decreased with filler, load, hardness and impact strength increased. TiO 2 coated composites showed better wear performance than ZnO coated composites [13]. The effects of different fiber reinforcements on the wear behavior were investigated in another study.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, it was observed that the addition of E-glass fibers increased the wear resistance and the mechanical properties of composite materials. Singh and Sıddhartha 10 investigated three-body abrasive wear and mechanical properties of TiO 2 - and ZnO-filled bi-directional E-glass fiber-based polyester composites. They observed that composite materials filled with TiO 2 had better wear properties than composite materials filled with ZnO.…”
Section: Introductionmentioning
confidence: 99%